Determination of the design velocity of the gas flow in coarse and fine filters with varying degrees of contamination in the paint booths - V. E. Zinurov; R. Ja. Bikkulov; A. V. Dmitriev; O. S. Dmitrieva; A. N. Nikolaev (Известия высших учебных заведений: Проблемы энергетики)
OBJECT. Determination of the design velocity of the gas flow in coarse and fine filters with varying degrees of contamination. METHODS. We carried experimental studies out to solve the problem. To exclude errors during the studies caused by marriage or other reasons, 3 samples of each of the coarse and fine filters (clean and used) were used. To determine the design speed, an experimental installation was assembled, presented in the work, which included an air duct, an air injection fan, a nozzle for measuring excess pressure in front of the filter under study, an air vent hole, filter samples, a ventilation grate and measuring instruments – a differential pressure gauge testo 510i and an anemometer testo 405i. RESULTS. The article describes the relevance of the topic, analyzes the change in the pressure drop in the duct when using spent and clean coarse and fine filters. They showed that an increase in their operational life is possible with the use of a multi-vortex separator, which can be installed as a preliminary stage of purification. CONCLUSION. The estimated gas flow velocity when using coarse filters is only 2 m/s. The estimated gas flow velocity when using fine filters is only 0.5 m/s. A comparison of the difference in the pressure drop in the duct when using coarse and fine (spent and clean) filters shows that coarse filters are more susceptible to dusty flow, i.e. the bulk of particles in the dusty flow at an enterprise with paint chambers are relatively large particles. Hydraulic resistance increases by 1.58 times.